Utility values among myopic patients in mainland China. - Li, S; Wang, G; Xu, Y; Gray, A; Chen, G (2014)
PURPOSE: To elicit utility values of adult myopic patients in mainland China. METHODS: A valid sample of 442 myopia patients (spherical equivalent at least -0.5 diopters) aged 17 to 44 years who were scheduled to undergo refractive surgery were recruited. Information on time trade-off ([TTO] years of life willing to sacrifice for treatment of myopia) and standard gamble (SG) for blindness (risk of blindness from therapy, willing to sacrifice for treatment of myopia) utility values and sociodemographic and clinical data were obtained. RESULTS: The mean utility values based on TTO and SG were 0.96 ± 0.05 (95% confidence interval [CI], 0.95 to 0.96; median, 0.98) and 0.93 ± 0.09 (95% CI, 0.92 to 0.94; median, 0.97), respectively. Myopic patients using contact lens had significantly higher TTO utility values than those wearing glasses (p < 0.001). There was no significant difference in the TTO and SG utility values by age, sex, occupation, educational levels, residence, reasons for refractive surgery, and severity and duration of myopia (p > 0.05). CONCLUSIONS: The TTO and SG produce similar mean utility values, but there is poor agreement between results for individuals from the two methods. Utility values associated with myopic patients obtained in this study or reported in the literature seem to be higher than those obtained for other ophthalmic conditions.